2008
DOI: 10.1021/ac801506d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Various pH and Temperature Conditions on the Stability of Azaspiracids and Their Importance in Preparative Isolation and Toxicological Studies

Abstract: Azaspiracids (AZAs) are a group of shellfish toxins that were discovered in mussels from Irish waters in 1995. Because of the rare occurrence of poisoning incidents, the toxicity of the compounds is a continued matter of debate. Neither their mechanism of action nor their pharmacokinetic behavior has been elucidated, principally because of the lack of standards and reference tissues. Procedures to isolate AZAs from contaminated shellfish or to synthesize them have been developed; in particular, the procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…McCarron et al (2009) demonstrated that one involved mechanism was the decarboxylation of several AZA analogues that contain a carboxylic function. Notwithstanding, Alfonso et al (2008) found that protein digestion of the tissues of AZA-containing mussels increases the amount of these toxins that could be extracted with MeOH, suggesting that protein denaturation during cooking could also contribute to the increase of AZAs concentration with this process.…”
Section: Toxin Contentmentioning
confidence: 98%
See 2 more Smart Citations
“…McCarron et al (2009) demonstrated that one involved mechanism was the decarboxylation of several AZA analogues that contain a carboxylic function. Notwithstanding, Alfonso et al (2008) found that protein digestion of the tissues of AZA-containing mussels increases the amount of these toxins that could be extracted with MeOH, suggesting that protein denaturation during cooking could also contribute to the increase of AZAs concentration with this process.…”
Section: Toxin Contentmentioning
confidence: 98%
“…The second one is the presence of nondetected toxin derivatives that could be converted to the main toxins by the thermal treatment, as was described with azaspiracids (Hess et al, 2005;McCarron et al, 2009). The third one is an incomplete detection of the toxin content in raw or steamed mussel (or in both) by the method used, as previously suggested, to explain the increase of concentration of some azaspiracids with cooking (Alfonso et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to potential stability problems of AZAs, PnTX-E and PTX2 in acidic conditions [39][40][41] (and the acid present in the certified calibrant to enhance storage capacity of 13-desmeSPX-C), three initial toxin mixtures were prepared in methanol: (i) Mix-1 containing PTX2, AZA1 to 3, OA, DTX1 and 2, PnTX-E, YTX, homo-YTX and DA; (ii) Mix-2 containing 13-desmeSPX-C, GYM-A, PnTX-F, PnTX-G and DA and (iii) BTX1,2-mix with BTX1 and BTX2. These stock solutions were then serially diluted in MeOH using a Hamilton Microlab diluter-dispenser (Hamilton Company, Reno, NV).…”
Section: Matrix-matched Calibration Solutions For the Evaluation Of Mmentioning
confidence: 99%
“…The presence of protein-bound AZAs was further suggested in a later work examining the stability of AZAs [43]. However, in studies conducted as part of this work, there was no evidence of significant amounts of protein-bound toxins in CRM-AZAMus; therefore, there is no perceived risk of changes to the certified concentrations (see Electronic Supplementary Material (ESM)).…”
Section: Homogeneity and Stabilitymentioning
confidence: 63%